Prognostic Alternative mRNA Splicing in Adrenocortical Carcinoma - Liang, Weiwei; Sun, Fangfang (Frontiers in Endocrinology, 2021)
Background. This paper aims to identify alternative RNA splicing landscape and its prognostic value in adrenocortical carcinoma. Methods. The alternative splicing events data with corresponding clinical information data of 79 ACC patients were obtained from the Cancer Genome Atlas and SpliceSeq package. Prognosis-associated AS events by using univariate Cox regression analysis were selected. Gene functional enrichment analysis demonstrated the potential pathways enriched by survival-associated AS. Prognosis-related splicing events were submitted to develop moderate predictors using Lasso regression model. Results. 1005 survival associated alternative splicing events were identified. The prognostic genes included ATXN2L, MEIS1, IKBKB, COX4I1. Functional enrichment analysis suggested that prognostic splicing events are associated with Wnt signaling pathway. A prediction model including 12 alternative splicing events was constructed by Lasso regression. ROC analysis showed good performance of the prediction model with AUC of 0.89. Then, a nomogram integrating the clinical-pathological factors and riskscore was constructed for predicting 1‐ and 3‐year survival rate. Conclusion. Our data provide a comprehensive bioinformatics analysis of AS events in ACC, providing biomarkers for disease progression and a potentially rich source of novel therapeutic targets.